TRADISI HAFLAH : INTEGRASI BUDAYA LOKAL DAN KEISLAMAN DI PONDOK PESANTREN AL ASY'ARIYAH WONOSOBO - Lia Amalia; Adi Prasetyo; Vava Iman Agus Faisal (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This study aims to describe the implementation of the Haflah tradition and analyze the form of integration of local culture and Islamic values ​​​​at the Al Asy'ariyah Wonosobo Islamic Boarding School. Adopting a descriptive qualitative method, data were gathered via observation, interviews, and documentation, with informants chosen through purposive and snowball sampling. Results indicate HKQ extends beyond celebrating students' Qur’an memorization achievements, acting as a platform for Islamic outreach and fostering ties between the pesantren and local society. Diverse events—including santri contests, napak tilas treks, grave visits, Hamalatul Qur’an, communal recitations, blood drives, and mass circumcisions—highlight the fusion of spiritual piety and social commitment. This practice is vital for upholding moderate Islam, bolstering students' faith identity, and preserving indigenous values against modernization pressures.